Implementasi Kewenangan KPP Pratama Tampan dalam Mencegah Wajib Pajak Melakukan Penghindaran Pajak di Pekanbaru - Aulia Hanyfah; Dodi Haryono; Separen Separen (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This research is motivated by the compliance level of Individual Taxpayers at the Pratama Tampan Tax Office (KPP) Pekanbaru, which still fluctuates from year to year, thus opening up opportunities for tax avoidance practices. The purpose of this research is to determine the implementation of authority by KPP Pratama Tampan in preventing taxpayers from committing tax avoidance in Pekanbaru, the obstacles faced in the exercise of such authority, and the efforts that have been made to prevent tax avoidance in the city of Pekanbaru. This research uses a sociological legal research method with descriptive nature, conducted at the Pratama Tampan Tax Office Pekanbaru. The data sources consist of primary data obtained through interviews and observations, and secondary data sourced from laws and regulations, books, journals, and related documents. Data collection techniques are carried out through interviews, observation, and literature study, then analyzed qualitatively and presented descriptively. The results show that the implementation of authority of KPP Pratama Tampan is exercised through four instruments, namely services, compliance supervision, tax audits, and administrative law enforcement based on a compliance risk management approach. The obstacles faced include the limited number of Account Representatives and Tax Auditors, suboptimal data integration between institutions, low taxpayer awareness, regulatory complexity, and the prevalence of the underground economy sector. Prevention efforts are pursued through preventive and repressive measures, as well as modernization of the administration system through the Coretax Administration System.